3a - 2b
3a - 2b
10a+7b undefined variables cannot be determined
What is the solution of -2a plus 3a plus 5b
-7a + 3a = -4a
a + 3a - 2 + 3a. Add the a + 3a + 3a = 7a. You can't combine the -2 & 7a so the solution is: 7a - 2.
3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b
3a + 5b - 6a - 9b = -3a - 4b
Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?
It is an expression that can be simplified to: 3a-2b+c
add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b
It is: 7a+1 when simplified
24am - 9an + 40bm - 15bn = 3a*(8m - 3n) + 5b*(8m - 3n) = (3a + 5b)*(8m - 3n)
15a - 25b + 20 = 5 (3a - 5b + 4)
4a + 3a = (4 + 3)a = 7a
It is: 3a+7a = 10a simplified
It is: 5(3a+b) when factored
7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a
ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.
5(3a - 5b + 4)
Clearly, there are some signs missing. So let's try the four possibilities for the second terms: 1. + and + 3a + 4b = 7a + 4b Subtract 4b from each side: 3a = 7a Subtract 3a from each side: 0 = 4a Answer : a = 0, b indeterminate (ie can have any vaue). 2. + and - 3a + 4b = 7a - 4b Subtract 4b from each side: 3a = 7a - 8b Subtract 7a from each side: -4a = -8b or 4a = 8b Answer: a = 2b 3. - and - 3a - 4b = 7a - 4b Add 4b to each side: 3a = 7a Subtract 3a from each side: 0 = 4a Answer : a = 0, b indeterminate (ie can have any vaue). 4. - and + 3a - 4b = 7a + 4b Add 4b to each side: 3a = 7a + 8b Subtract 7a from each side: -4a = 8b or 4a = -8b Answer: a = -2b Can't do better than that with the information available.
45(3a + 5b)
a + 7b + 2c